Tingkat Pengetahuan Dokter Gigi Mengenai Radiologi Forensik Kedokteran Gigi (Kajian pada Dokter Gigi di Jakarta Barat) - Mariyah; Rizki Tanjung; Intan Farizka (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: A dentist is able to be requested for help investigating a crime handled by the authorities. Hence, the knowledge of forensic odontology has to be possessed by not only forensic dentists but also all practicing dentists require having the knowledge. Dental identification is the most general method used in forensic odontology, not only tooth; dental radiology can also be used. Radiographic methods are often used because this method is relatively easy, the technique is efficient, recordings can be obtained both on and off, and it is more economical than DNA technology. Radiographs have been proven and considered valid in court. Purpose: To obtain an overview of the knowledge of dentists in West Jakarta regarding the use of radiology on forensic odontology. Method: Descriptive observational study with cross sectional design conducted through online. The data collected from 99 respondents, all are dentists who practice in West Jakarta. A questionnaire used to measure the dentists’ knowledge. It consists of 11 closed-ended questions; score 2 given for correct answer, score 1 given for incorrect answer. Result: The result of data calculation from respondents’ answers was divided into three knowledge categories. The study obtained 30.3 % respondents have good knowledge, 36.4% respondents have adequate knowledge, and 33.3% respondents have lack knowledge. Conclusion: Based on the research data calculation, 36 respondents (36.4%) have adequate knowledge (56%-75%).